Rearing of Trichogramma cordubensis Vargas & Cabello (Hym., Trichogrammatidae) on Mediterranean flour moth cold-stored eggs - Vieira, Virgílio (1995)
The influence of Ephestia kuehniella Zeller (Lep.: Pyralidae) cold-stored eggs on several biological parameters of Trichogramma cordubensis Vargas & Cabello is studied. These eggs, stored at 0.7°C for 4.5 months, proved acceptable as well as suitable for longevity and rate of emergence of the parasitoid. Moreover, no differences were found between the number of parasitized eggs by T. cordubensis females reared during seven consecutive generations on cold-stored eggs and by females reared on UV-irradiated eggs. Suitability declined as storage time increased. This result is likely due to a lost of host egg weight. However, treatment of E. kuehniella eggs leads to some advantages, including an enlargement of the duration of storage, and a reduction of the associated cost (suppression of UV irradiation).